2014
DOI: 10.3109/00365513.2014.965735
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on haemostasis in whole blood from ticagrelor- and aspirin-treated patients with acute coronary syndrome

Abstract: In acute coronary syndrome patients treated with ticagrelor and aspirin, in vitro hypothermia to 33°C markedly increased platelet activity measured with flow cytometry, whereas viscoelastic coagulation test (Sonoclot) revealed a hypocoagulative response. Prospective clinical trials studying platelet inhibition at different temperatures and correlating changes in platelet function to bleeding or stent occlusion are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…The authors explained that Sonoclot and thromboelastography fail to detect changes in platelet activation, whereas flow cytometry is designed to do this. Similar conflicting results were found in respect to TH and ticagrelor based on in vivo and in vitro designs . This finding is particularly interesting due to the unique study design, in which researchers eliminated the possible risk of poor intestinal absorption on the outcome .…”
Section: Th and Asamentioning
confidence: 58%
See 3 more Smart Citations
“…The authors explained that Sonoclot and thromboelastography fail to detect changes in platelet activation, whereas flow cytometry is designed to do this. Similar conflicting results were found in respect to TH and ticagrelor based on in vivo and in vitro designs . This finding is particularly interesting due to the unique study design, in which researchers eliminated the possible risk of poor intestinal absorption on the outcome .…”
Section: Th and Asamentioning
confidence: 58%
“…The effect of P2Y 12 ‐antagonists can be detected with flow cytometry–based VASP analysis and, as described above, it was decreased when clopidogrel was given during mild hypothermia . This can explain the discrepant findings between Multiplate and Sonoclot with VASP analyses in the study conducted by Kander et al . Moreover, a strong correlation between gastric emptying and VASP during hypothermia indicated that delayed gastric emptying could be responsible for the limited ticagrelor effect.…”
Section: Th and P2y12 Inhibitorsmentioning
confidence: 95%
See 2 more Smart Citations
“…This study concluded that, operation time, diameter, length or number of stent showed no significant difference in the groups. Interventional operation itself also has important influence on the function of blood coagulation system (14). Test time of blood coagulation, postoperative CK-MB, cTnI and BNP levels in observation group are significantly lower than that of control group.…”
Section: Discussionmentioning
confidence: 99%